Meralgia Paresthetica Review: Update on Presentation, Pathophysiology, and Treatment - Yanet de la Caridad Gomez; Edgar Remotti; Deandra Uju Momah; Emily Zhang; Daniel D. Swanson; Rosa Kim; Ivan Urits; Alan D. Kaye; Christopher L Robinson (Health Psychology Research)
# Purpose of Review